GURAU PAUAH - Try Wahyu Purnomo; Wimbrayardi Wimbrayardi; Marzam Marzam (SENDRATASIK UNP, 2014)
Abstract This music work is an innovative art taken from Pado-pado rhytm in Saluang Pauah show. This music work was was arranged based on the consept of the rhytm and melody combination of any traditional music tools (Saluang Pauah, talempong, canang, adok, djembe) and modern ones (Bass, electric guitar, piano, percussion set, conga, violin, viola and cello). Technically, the melody of Pado-pado is used as the main melody which was further developed into three compositions. Kata Kunci: Karya Seni, Gurau, Pauah, Saluang Pauah